ANALYSIS OF POLYMER COMPOSITE MATERIALS FOR SLIDING BEARINGS - Marchuk, Roman; Mnatsakanov, Rudolf (Problems of Friction and Wear, 2023)
The mechanical and tribotechnical characteristics of polymer materials are analyzed and the possibility of their improvement by adding reinforcing substances is shown. For Teflon-based composite materials, no change in antifriction properties has been established under lubrication conditions, compared to friction conditions without lubrication, the friction coefficient is reduced by only 1-3%. Effective fillers of polymer materials include carbon fibers, MoS2. , graphite, graphene, SiO2, etc. It was analyzed that the addition of silicon carbide to polyvinyl chloride increases the anti-friction characteristics, heat resistance and dielectric properties of the polymer. Antifriction materials based on polyvinyl chloride have a relatively low coefficient of friction, but it can be improved if silicon carbide is dispersed on the surface of the polymer. It is substantiated that knowledge of the mechanical and tribotechnical characteristics of interacting tribomaterials is necessary for their selection from the point of view of the safety and efficiency of sliding bearings in the machine-building industry.